Pseudophosphatase STYX promotes tumor growth and metastasis by inhibiting FBXW7 function in colorectal cancer. (10th July 2019) - He, Diao; Ma, Zida; Fang, Chao; Ding, Jingjing; Yang, Wenming; Chen, Peng; Huang, Libin; Wang, Cun; Yu, Yongyang; Yang, Lie; Li, Yuan; Zhou, Zongguang
Abstract: Serine/threonine/tyrosine interacting protein (STYX), a member of protein tyrosine phosphatases, has recently been reported as a potential oncogene. However, the role of STYX in colorectal cancer (CRC) remains unknown. In this study, we found that STYX was highly expressed in CRC tissues and closely correlated with tumor development and survival of CRC patients. In vitro studies showed that overexpression of STYX promoted proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) and inhibited apoptosis in CRC cells, while STYX knockdown had the opposite effects. Consistently, in vivo experiments showed that overexpression of STYX promoted tumor growth and lung metastasis. Mechanically, STYX bound to the F-box and WD repeat domain-containing7 (FBXW7) protein and inhibited its function. Co-regulation of STYX and FBXW7 expression reversed the biological changes mediated by regulation of STYX expression alone in CRC cells. Additionally, FBXW7 expression was negatively associated with STYX expression in CRC tissues, and low STYX levels accompanying high FBXW7 levels predicted favorable prognosis of CRC patients. In conclusion, our results suggest that STYX plays an oncogenic role by inhibiting FBXW7 and represents a potential therapeutic target and prognostic biomarker in CRC. Highlights: STYX is frequently up-regulated in CRC tumor tissues. STYX overexpression favors CRC cell growth and metastasis in vitro and in vivo. STYX regulates CRC growth and metastasis by targeting FBXW7. Combination of STYX and FBXW7 expression predicts tumor stages and prognosis more precisely.